Multi-performative façade systems: The case of real-time adaptive BIPV shading systems to enhance energy generation potential and visual comfort - Biloria, Nimish; Makki, Mohammed; Abdollahzadeh, Nastaran (Frontiers in Built Environment, 2023)
Building envelopes invariably tend to be static systems that encounter various performance limitations such as inefficient illuminance admittance, and heat and moisture transmission owing to their non -responsiveness towards environmental fluctuations. In contrast to such façade solutions, responsive façade systems with embedded sensing, actuation, and control systems have been proven to perform with up to 65% higher efficiency (Dewidar et al., 2010) by being able to adapt their physical characters, such as orientation, and material property in real-time as a response to fluctuating environmental conditions (visual and thermal) and user preferences. Advancements in artificial intelligence and machine learning processes further aid such responsive façade systems to optimize multiple parameters such as illuminance level and the associated lighting energy, visual discomfort caused by solar glare, solar heat gain, thermal resistance (heating energy and comfort level), and natural ventilation simultaneously. This chapter investigates the case of a real-time adaptive BIPV shading system and its ability (in comparison with traditional static BIPV façade systems) to perform as regards visual comfort and energy generation potential simultaneously within the humid subtropical climate of Sydney, Australia. A simulated case scenario wherein a real-time adaptive BIPV shading systems is deployed on a typical multistorey building façade in Sydney, Australia is accordingly presented. The conducted simulation considers the responsive BIPV system as a double-skin façade system and uses multi-objective evolutionary computing principles to decipher its integrability potential. A comparative analysis between traditional static mounted PV systems as opposed to multi-objective optimization driven real-time adaptive BIPV shading configurations is subsequently presented. The ability to maximize generated energy, while simultaneously maintain visual comfort is thus a unique proposition of this chapter.